Front Street, Dawson, Yukon Territory, in the moonlight, ca. 1898. - University of Washington Libraries. Special Collections Division
Caption on image: "First Ave. Dawson by moonlight" PH Coll 246.49 [Meed journal: "Front Street (First Ave), Dawson Y.T. photographed in winter by moonlight."]. Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number